Carbocatalytic Oxidative Dehydrogenative Couplings of (Hetero)Aryls by Oxidized Multi‐Walled Carbon Nanotubes in Liquid Phase. Issue 53 (29th August 2019) - Wirtanen, Tom; Aikonen, Santeri; Muuronen, Mikko; Melchionna, Michele; Kemell, Marianna; Davodi, Fatemeh; Kallio, Tanja; Hu, Tao; Helaja, Juho
Abstract: HNO3 ‐oxidized carbon nanotubes catalyze oxidative dehydrogenative (ODH) carbon–carbon bond formation between electron‐rich (hetero)aryls with O2 as a terminal oxidant. The recyclable carbocatalytic method provides a convenient and an operationally easy synthetic protocol for accessing various benzofused homodimers, biaryls, triphenylenes, and related benzofused heteroaryls that are highly useful frameworks for material chemistry applications. Carbonyls/quinones are the catalytically active site of the carbocatalyst as indicated by model compounds and titration experiments. Further investigations of the reaction mechanism with a combination of experimental and DFT methods support the competing nature of acid‐catalyzed and radical cationic ODHs, and indicate that both mechanisms operate with the current material. Abstract : Catalysis with carbon material : HNO3 ‐oxidized carbon nanotubes catalyze oxidative dehydrogenative (ODH) carbon–carbon bond formation between electron‐rich (hetero)aryls with O2 as a terminal oxidant.